Apparel in South Asia - Lopez-Acevedo, Gladys; Robertson, Raymond (World Bank, Washington, DC, 2016)
Apparel is the largest labor-intensive manufacturing industry in South Asia, and is a major employer of women. Although South Asia’s apparel sector benefits from many of the same favorable conditions as East Asia’s, performance in South Asian apparel remains well below that of East Asia. The objective of this study is to identify the policy changes necessary for South Asia to capitalize on this opportunity. The authors review the apparel sectors in Bangladesh, India, Pakistan and Sri Lanka, and compare them with Vietnam and China. The report uses quantitative data (analysis based on a gravity model, enterprise and buyer surveys) and qualitative information (interviews with leading firms) to identify changes in policies that would enable South Asia to meet the requirements of global buyers. Low productivity and poor trade logistics make it difficult for South Asia’s apparel sector to compete in global markets, despite a cost advantage due to lower wages than other major exporters. Leading firms exhibit that world class operational performance can be achieved in South Asia by investing in training and technology. These firms overcame constraints in the external environment by achieving economies of scale, and in the case of India and Pakistan, by integrating vertically to avoid barriers to sourcing high-quality inputs on the global market. All countries should promote Plug and Play industrial zones with ready to use industrial buildings and facilities to promote women labor force participation, as female workers would be the main beneficiaries of growth in apparel production.